Radio‐morphology: Parametric shape‐based features in radiotherapy. Issue 2 (24th December 2018) - Lakshminarayanan, Pranav; Jiang, Wei; Robertson, Scott P.; Cheng, Zhi; Han, Peijin; Bowers, Michael; Moore, Joseph A.; Shpitser, Ilya; Siddiqui, Sauleh A.; Quon, Harry; Taylor, Russell H.; McNutt, Todd
Abstract : Purpose: In radiotherapy, it is necessary to characterize dose over the patient anatomy to target areas and organs at risk. Current tools provide methods to describe dose in terms of percentage of volume and magnitude of dose, but are limited by assumptions of anatomical homogeneity within a region of interest (ROI) and provide a non‐spatially aware description of dose. A practice termed radio‐morphology is proposed as a method to apply anatomical knowledge to parametrically derive new shapes and substructures from a normalized set of anatomy, ensuring consistently identifiable spatially aware features of the dose across a patient set. Methods: Radio‐morphologic (RM) features are derived from a three‐step procedure: anatomy normalization, shape transformation, and dose calculation. Predefined ROI's are mapped to a common anatomy, a series of geometric transformations are applied to create new structures, and dose is overlaid to the new images to extract dosimetric features; this feature computation pipeline characterizes patient treatment with greater anatomic specificity than current methods. Results: Examples of applications of this framework to derive structures include concentric shells based around expansions and contractions of the parotid glands, separation of the esophagus into slices along the z ‐axis, and creating radial sectors to approximate neurovascular bundles surrounding the prostate. Compared to organ‐level dose‐volume histograms (DVHs), using derived RM structures permits a greater level of control over the shapes and anatomical regions that are studied and ensures that all new structures are consistently identified. Using machine learning methods, these derived dose features can help uncover dose dependencies of inter‐ and intra‐organ regions. Voxel‐based and shape‐based analysis of the parotid and submandibular glands identified regions that were predictive of the development of high‐grade xerostomia (CTCAE grade 2 or greater) at 3–6 months post treatment. Conclusions: Radio‐morphology is a valuable data mining tool that approaches radiotherapy data in a new way, improving the study of radiotherapy to potentially improve prognostic and predictive accuracy. Further applications of this methodology include the use of parametrically derived sub‐volumes to drive radiotherapy treatment planning.